Analysis of Financial Management to Enhance Profitability in Micro, Small, and Medium Enterprises (MSMEs) - Zendrato, Minta Wati; Octafian, Ray (MultiTech Publisher, 2025)
This study seeks to examine financial management to enhance the profitability of Micro, Small, and Medium Enterprises (MSMEs) through a qualitative methodology. A case study was performed at Toko Barokah, Gembongan, Karangjati, an MSME within the trading sector. Effective financial management is crucial for the success of a business, particularly for MSMEs that frequently encounter difficulties in cash flow management, financial record-keeping, and financial decision-making. Data for the research was gathered via comprehensive interviews, observations, and documentation. The findings indicated that Toko Barokah continues to encounter multiple challenges in financial management, including disorganized transaction records, inadequate differentiation between personal and business finances, and limited utilization of financial technology. These limitations hinder the store's capacity to optimize profitability. Nonetheless, there are contributing factors, including the business owner's dedication to acquiring financial management skills and the substantial market potential that remains untapped. This study advocates for enhancing financial record-keeping through the utilization of straightforward applications, offering financial training to entrepreneurs, and adopting superior cash flow management techniques. By implementing these measures, Toko Barokah is anticipated to enhance its profitability sustainably. This research offers valuable insights for other MSMEs in effectively managing finances to facilitate business growth